Are caregiving responsibilities associated with non-attendance at breast screening? - Mairs Adrian; Hall Clare; Rosato Michael; Connolly Sheelah; Kinnear Heather; O'Reilly Dermot (BMC, 2010)
Abstract Background Previous research showed that deprived individuals are less likely to attend breast screening and those providing intense amounts of informal care tend to be more deprived than non-caregivers. The aim of this study was to examine the relationship between informal caregiving and uptake of breast screening and to determine if socio-economic gradients in screening attendance were explained by caregiving responsibilities. Methods A database of breast screening histories was linked to the Northern Ireland Longitudinal Study, which links information from census, vital events and health registration datasets. The cohort included women aged 47 - 64 at the time of the census eligible for breast screening in a three-year follow-up period. Cohort attributes were recorded at the Census. Multivariate logistic regression was used to examine the relationship between informal caregiving and uptake of screening using STATA version 10. Results 37,211 women were invited for breast screening of whom 27,909 (75%) attended; 23.9% of the cohort were caregivers. Caregivers providing <20 hours of care/week were more affluent, while those providing >50 hours/week were more deprived than non-caregivers. Deprived women were significantly less likely to attend breast screening; however, this was not explained by caregiving responsibilities as caregivers were as likely as non-caregivers to attend (Odds Ratio 0.97; 95% confidence intervals 0.88, 1.06). Conclusions While those providing the most significant amounts of care tended to be more deprived, caregiving responsibilities themselves did not explain the known socio-economic gradients in breast screening attendance. More work is required to identify why more deprived women are less likely to attend breast screening.